A Review on Benefits of Homestay Tourism in Nepal - Gautam, Biranji (Kalika Journal of Multidisciplinary Studies, 2024)
Homestay tourism in Nepal has become a prominent and sustainable model, offering a range of socio-economic, cultural, and environmental benefits. This review explores how homestays contribute to these areas, highlighting examples from across the country. Since the introduction of homestays in Sirubari in 1997, the model has expanded to over 200 homestays across 60 districts. Google Scholar, Web of Science, Research gate, JSTOR, and Scopus using keywords like “homestay tourism in Nepal” and “benefits of homestay tourism.” Relevant peerreviewed articles, reports, and literature published between 2010 and 2024 were included. Homestays in various regions provide tourists with immersive experiences in ethnic cultures, including traditional festivals and local crafts, which help preserve cultural heritage and build community pride. Economically, these homestays generate essential income for local families, improve access to education and healthcare, and boost local businesses through increased demand for goods and services. Environmentally, homestays adopt sustainable practices such as waste reduction and solar energy use, with tourism revenue supporting conservation projects like reforestation and wildlife protection. By aligning with global trends toward responsible tourism, homestays reduce ecological impact and foster meaningful interactions between tourists and hosts. The review recommends implementing comprehensive training programs for homestay operators to enhance sustainable practices and maximize benefits, ensuring the long-term success and positive impact of homestay tourism in Nepal.